This action might not be possible to undo. Are you sure you want to continue?

4

The Hyperbolic Functions

These are constructed from the exponential function, but obey identities closely analogous to those satisﬁed by the corresponding trigonometric functions (obtained by dropping the ﬁnal “h”).

2.4.1

Deﬁnitions

cosh x = sinh x = 1 x (e + e−x ), 2 1 x (e ¡ e−x ), 2 ex ¡ e−x 1 ¡ e−2x e2x ¡ 1 , = = 2x ex + e−x 1 + e−2x e +1 ex + e−x 1 + e−2x e2x + 1 = = 2x ex ¡ e−x 1 ¡ e−2x e ¡1 2 , x + e−x e 2 (x 6= 0). x ¡ e−x e (2.31) (2.32) (2.33) (x 6= 0),(2.34) (2.35) (2.36)

sinh x cosh x cosh x 1 = coth x = tanh x sinh x 1 sech x = cosh x 1 cosech x = sinh x tanh x =

= = = =

2.4.2

The Fundamental Identity

Corresponding to the well-known identity cos2 x + sin2 x = 1 for the trigonometric functions, we have for the hyperbolic functions the identity cosh2 x ¡ sinh2 x = 1 (2.37)

(holding for all real x). NB the minus sign! To prove (2.37), just substitute the deﬁnitions (2.31) and (2.32) into the LHS, to get 1 x −x 2 1 x −x 2 1 2x −2x 1 (e +e ) ¡ (e ¡e ) = (e +e +2ex e−x )¡ (e2x +e−2x ¡2ex e−x ) = ex e−x = ex−x = e0 = 1. 4 4 4 4

22

2.4.3

Further Identities

1 ¡ tanh2 x coth2 x ¡ 1 sinh(x + y) sinh(x ¡ y) cosh(x + y) cosh(x ¡ y) sinh 2x cosh 2x = = = = = = = = sech2 x, cosech2 x, sinh x cosh y + cosh x sinh y, sinh x cosh y ¡ cosh x sinh y, cosh x cosh y + sinh x sinh y, cosh x cosh y ¡ sinh x sinh y, 2 sinh x cosh x, sinh2 x + cosh2 x, 1 (cosh 2x + 1), 2 1 (cosh 2x ¡ 1), 2 1 [sinh (x + y) + sinh (x ¡ y)] , 2 1 [cosh (x + y) + cosh (x ¡ y)] , 2 1 [cosh (x + y) ¡ cosh (x ¡ y)] . 2 (2.38) (2.39) (2.40) (2.41) (2.42) (2.43) (2.44) (2.45) (2.46) (2.47) (2.48) (2.49) (2.50)

cosh2 x = sinh2 x = sinh x cosh y = cosh x cosh y = sinh x sinh y =

Each of these has a trigonometric counterpart (see Appendix C), but there are some important diﬀerences of sign, which should be carefully noted. The identities are all easy to prove from the deﬁnitions above.

2.4.4

The Graphs of cosh, sinh and tanh

Using the deﬁnitions of the hyperbolic functions, and our knowledge of the exponential function, we can sketch the following graphs and deduce some properties for the hyperbolic functions.

23

cosh 0 = 1, cosh x ! +1 as x ! §1, cosh (¡x) = cosh (x) (i.e. it is an EVEN function).

24

sinh 0 sinh x sinh x sinh (¡x)

= ! ! =

0, +1 as x ! +1, ¡1 as x ! ¡1, ¡ sinh (x) (i.e. it is an ODD function).

tanh 0 tanh x tanh x tanh (¡x)

= ! ! =

0, +1 as x ! +1, ¡1 as x ! ¡1, ¡ tanh (x) (i.e. it is an ODD function).

Like all even functions, cosh has a a graph which is symmetrical about Oy, i.e. invariant under reﬂection in Oy. It has a minimum value of 1 at x = 0, where its derivative sinh x is zero. On the other hand, the graphs of the functions sinh and tanh, like those of all odd functions, are invariant under rotation through 180◦ about O. Note that sinh and tanh are both increasing functions and that the graph of tanh has horizontal asymptotes y = §1 approached as x ! §1 respectively.

2.4.5

Symmetry and Asymptotic Properties of other hyperbolic functions

Similarly, we can deduce the following properties of coth, sech and cosech: coth(¡x) = ¡ coth x, sech (¡x) = sechx, cosech (¡x) = ¡cosechx.

25

coth x ! 1 as x ! +1, coth x ! +1 as x ! 0 from above , sech x ! 0 cosech x ! 0 sech 0 = 1 cosech x ! +1 as x ! 0 from above,

coth x ! ¡1 as x ! ¡1, coth x ! ¡1 as x ! 0, from below, as x ! §1, as x ! §1, cosech x ! ¡1 as x ! 0 from below.

26

Sign up to vote on this title

UsefulNot useful2.4
The Hyperbolic Functions
These are constructed from the exponential function, but obey identities closely analogous to those satisﬁed by the corresponding trigonometric functions (obtained by...

2.4

The Hyperbolic Functions

These are constructed from the exponential function, but obey identities closely analogous to those satisﬁed by the corresponding trigonometric functions (obtained by dropping the ﬁnal “h”).

2.4.1

Deﬁnitions

cosh x = sinh x = 1 x (e + e−x ), 2 1 x (e ¡ e−x ), 2 ex ¡ e−x 1 ¡ e−2x e2x ¡ 1 , = = 2x ex + e−x 1 + e−2x e +1 ex + e−x 1 + e−2x e2x + 1 = = 2x ex ¡ e−x 1 ¡ e−2x e ¡1 2 , x + e−x e 2 (x 6= 0). x ¡ e−x e (2.31) (2.32) (2.33) (x 6= 0),(2.34) (2.35) (2.36)

sin

The Hyperbolic Functions

These are constructed from the exponential function, but obey identities closely analogous to those satisﬁed by the corresponding trigonometric functions (obtained by dropping the ﬁnal “h”).

2.4.1

Deﬁnitions

cosh x = sinh x = 1 x (e + e−x ), 2 1 x (e ¡ e−x ), 2 ex ¡ e−x 1 ¡ e−2x e2x ¡ 1 , = = 2x ex + e−x 1 + e−2x e +1 ex + e−x 1 + e−2x e2x + 1 = = 2x ex ¡ e−x 1 ¡ e−2x e ¡1 2 , x + e−x e 2 (x 6= 0). x ¡ e−x e (2.31) (2.32) (2.33) (x 6= 0),(2.34) (2.35) (2.36)

sin

- Hyperbolic Functions
- spe 2002 anss
- trigonometric identities.docx
- ex.01.ans
- Maths 1A - Chapter Wise Important Questions
- SANTALÓ 155
- simp
- A2 Maths Questions
- Matematika Teknik
- Advance_differential_equation_MAT565_pas.pdf
- QA
- Emmanuel Yomba- Construction of new solutions to the fully nonlinear generalized Camassa-Holm equations by an indirect F function method
- AQA-MFP2-W-MS-JUN07
- Exponential
- 608a-13
- 4 Vectors
- Exponential Function
- Statistical mechanics lecture notes (2006), L14
- Excel Material
- Algebra 2 Lesson Plan 5.5 Final
- Temporal Expressions
- Thermal Modulation of Rayleigh-Benard Convection
- 7_7 Exponential Growth - Decay
- Sol1_1stOrderODE(2)
- 2007que
- Elementary Differential Equations Book
- Core 3 Revision Pack
- Lecture2.pdf
- Components or Resolved Forces
- NEWS_Answer and Solution for WBJEE -2010_wbjee_4_18_51
- Hyperbolic Notes